2018
DOI: 10.1513/annalsats.201804-255oc
|View full text |Cite
|
Sign up to set email alerts
|

Role of Comorbidities in Treatment and Outcomes after Chronic Obstructive Pulmonary Disease Exacerbations

Abstract: Comorbidity was associated with 30-day readmission and mortality, and with delivery of fewer treatments known to be beneficial among patients with COPD exacerbation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
17
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 33 publications
(20 citation statements)
references
References 40 publications
2
17
0
1
Order By: Relevance
“…Many other comorbidities were also reported (tables S2 and S3). Four studies [22,38,43,47] used the comorbidity index to assess comorbidities. SPECE et al [47] found that each one-point increase in comorbidity index was associated with a 24% increased risk of readmission or death: OR 1.24 (95% CI 1.18-1.30).…”
Section: Meta-analysis Resultsmentioning
confidence: 99%
“…Many other comorbidities were also reported (tables S2 and S3). Four studies [22,38,43,47] used the comorbidity index to assess comorbidities. SPECE et al [47] found that each one-point increase in comorbidity index was associated with a 24% increased risk of readmission or death: OR 1.24 (95% CI 1.18-1.30).…”
Section: Meta-analysis Resultsmentioning
confidence: 99%
“…The baseline subjects seemed to have higher comorbidity scores, whereas the postbundle subjects had lower percent of predicted FEV 1 , both of which increase the risk of ED revisit. 35,36 Lastly, the revisit rates are assessed by individual encounters rather than by individual subjects. Frequent ED utilization is common among individual subjects with COPD, and some subjects had more than one encounter in our system throughout the study period.…”
Section: Discussionmentioning
confidence: 99%
“…COPD is a disease associated with many co-morbidities and also with high mortality. [6] Advanced COPD is associated with weight loss. [7] Malnourished patients of COPD have increased risk of in-hospital deaths and of readmission.…”
Section: Discussionmentioning
confidence: 99%